2018
DOI: 10.17116/patol201880334-39
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary lactotroph adenomas resistant to dopamine agonist treatment: histological and immunohistochemical characteristics

Abstract: PLAs resistant to dopamine agonists in addition to PRL (100%) can express GH in 16% of cases are characterized by the immunoexpression of DR (42%) and ERα (32%), a low proliferative activity, increased angiogenesis in the adenomas with parasellar growth and invasion into the cavernous sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…Lu et al found that the preoperative PRL levels in the Ki-67 index >3% group remained significantly higher compared to those in patients with the Ki-67 index <3% group (p < 0.05) (44). Fedorova et al (45) and Zielinski et al (46) confirmed a positive correlation between the Ki-67 index and preoperative prolactin concentration in patients with prolactinoma. Li et al proposed that ethanol altered hypothalamic neurotransmitter levels and stimulated anterior pituitary cell proliferation, which further increased the prolactin level in cells and the secretory output of prolactin (47).…”
Section: Discussionmentioning
confidence: 86%
“…Lu et al found that the preoperative PRL levels in the Ki-67 index >3% group remained significantly higher compared to those in patients with the Ki-67 index <3% group (p < 0.05) (44). Fedorova et al (45) and Zielinski et al (46) confirmed a positive correlation between the Ki-67 index and preoperative prolactin concentration in patients with prolactinoma. Li et al proposed that ethanol altered hypothalamic neurotransmitter levels and stimulated anterior pituitary cell proliferation, which further increased the prolactin level in cells and the secretory output of prolactin (47).…”
Section: Discussionmentioning
confidence: 86%
“…In clinical practice, patients with prolactinomas are administered bromocriptine as the first line of treatment. Once resistance occurs, fulvestrant alone is usually administrated as an alternative therapeutic strategy; however, the response is often unsatisfactory 6 , 7 , 23 , 27 . Fulvestrant is a synthetic estrogen receptor antagonist, fulvestrant binds competitively to estrogen receptors and results in estrogen receptor deformation and decreased estrogen binding.…”
Section: Discussionmentioning
confidence: 99%
“…Prolactinomas are the most predominant type of functional pituitary adenoma, constituting ~40% of total pituitary adenomas globally 4 , 5 . Over the past decades, there have been substantial breakthroughs in the understanding and management of prolactinomas; bromocriptine is the first line treatment for prolactinomas, yet 30% of patients ultimately develop resistance 3 , 6 , 7 . These clinical phenomena highlight an urgent requirement for alternative treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Учитывая высокую встречаемость пролактин-секретирующих аденом, значительный вклад данного заболевания в уменьшение репродуктивного потенциала популяции и снижение качества жизни, решение проблемы гиперпролактинемии является важным аспектом общественного здоровья и позитивного тренда демографической ситуации [ 9 ][ 10 ]. В настоящее время возможности применения альтернативных методов лечения у пациентов, резистентных к агонистам дофамина, ограничены: лучевая терапия малоэффективна [ 11 ][ 12 ], радикальная операция в большинстве случаев невозможна в связи с тенденцией пролактин-секретирующих аденом гипофиза к параселлярному распространению и экспансивному росту [ 6 ]. Таким образом, наиболее перспективным направлением в ведении резистентных пациентов является применение медикаментозной терапии, в том числе — сочетанной и комбинированной.…”
Section: Discussionunclassified